2015
DOI: 10.12968/bjnn.2015.11.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Using environment modification and doll therapy in dementia

Abstract: Given the rise in the global number of people with dementia, the need for interventions to reduce the behavioural and psychological symptoms of dementia (BPSD) is ever present. This paper explores the evidence for the effectiveness of two non-pharmacological approaches; doll therapy and environment modification, to reduce behavioural and psychological symptoms of dementia. The evidence base is relatively weak owing to the small number of studies on this topic and the lack of rigor of the methodologies used. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Further, the staff was taught to use person-centered approaches to address BPSD with a variety of intervention options as delineated in the nursinghometoolkit.com. A toolkit approach that provides a variety of interventions to manage BPSD has also previously been shown to be more useful 56 than a single intervention implemented with all residents such as simulated presence 60 or passive music therapy. 61…”
Section: Discussionmentioning
confidence: 99%
“…Further, the staff was taught to use person-centered approaches to address BPSD with a variety of intervention options as delineated in the nursinghometoolkit.com. A toolkit approach that provides a variety of interventions to manage BPSD has also previously been shown to be more useful 56 than a single intervention implemented with all residents such as simulated presence 60 or passive music therapy. 61…”
Section: Discussionmentioning
confidence: 99%
“…Twelve articles assessed as having medium to strong quality evidence were identified using the search term 'doll' (mean REA score = 19.5, strong). Despite some staff and family members viewing dolls as patronising or infantilising (Hubbard & Olsen, 2016;Braden & Gaspar, 2015;Shin, 2015;Hahn, 2015;Mitchell & Templeton, 2014;James, Mackenzie, & Mukaetova-Ladinska, 2006;Alander, Prescott, & James, 2015), all 12 articles agreed regarding the positive impact of offering dolls to care home residents with dementia, including: improved communication and social interaction (Ng, Ho, Koh, Tan, & Chan, 2017;Mitchell, McCormack, and McCance, 2016;Alander et al 2015;Shin, 2015;Bisiani & Angus, 2013;Cohen-Mansfield, Marx, Dakheel-Ali, Regier, and Thein, 2010); reduced anxiety (Alander et al 2015;Bisiani & Angus, 2013); and reduction in behavioural and psychological symptoms of dementia (Cantarella, Borella, Faggian, Navuzzi, & De Beni, 2018). Mitchell et al (2016) reported an improvement in eating, however, Cantarella et al (2018) did not.…”
Section: Dollsmentioning
confidence: 99%